Katya & the prince of Siam - Hunter, Eileen; Narisa Chakrabongse Mom Rajawongse 1956- (River books, 1994)
Biography of Phitsanulōkprachānāt, Prince, son of Chulalongkorn, King of Siam, 1882-1920, and his wife, Ekaterina Ivanovna Desnitsky, 1888-1960.
Keywords: Desnitsky, Ekaterina Ivanovna <1888-1960>; Phitsanulōkprachānāt <Prince, son of Chulalongkorn, King of Siam, 1882-1920>; Desnitsky, Ekaterina I. -- 1888-1960; Chula Chakrabongse -- Siam, Prinz -- 1907-1963; Vorstenhuizen; Princes -- Thailand -- Biography; Wives -- Thailand -- Biography; Geschichte; Biografie